The Sigma-2 Receptor Selective Agonist Siramesine (Lu 28-179) Decreases Cocaine-Reinforced Pavlovian Learning and Alters Glutamatergic and Dopaminergic Input to the Striatum - Klawonn, Anna M.; Nilsson, Anna; Rådberg, Carl F.; Lindström, Sarah H.; Ericson, Mia; Granseth, Björn; Engblom, David; Fritz, Michael (Frontiers in Pharmacology, 2017)
Drug Addiction is a chronic, debilitating disease that affects millions of people around the world causing a substantial societal burden. Despite decades of research efforts, treatment possibilities remain limited and relapse represents the most treatment-resistant element. Neurosteroid sigma-1 receptors have been meticulously studied in psychostimulant reinforced Pavlovian learning, while the sigma-2 receptor subtype has remained unexplored. Recent development of selective sigma-2 receptor ligands have now made it possible to investigate if the sigma-2 receptor system is a potential target to treat drug addiction. We examined the effect of the sigma-2 receptor agonist Siramesine (Lu 28-179) on cocaine-associated locomotion, Pavlovian learning and reward neurocircuitry using electrophysiology recordings and in vivo microdialysis. We found that Siramesine significantly attenuated conditioned place preference acquisition and expression, as well as it completely blocked cocaine-primed reinstatement. Siramesine, in a similar manner as the selective sigma-1 receptor antagonist BD 1063, decreased acute locomotor responses to cocaine. Immunohistochemistry suggests co-expression of PGRMC1/sigma-2 receptors and VGLUT1 in presynaptic boutons of the Nucleus accumbens. Whole-cell voltage clamp recordings of neurons in the nucleus accumbens indicated that Siramesine decreases the presynaptic release probability of glutamate. Further, we demonstrated, via in vivo microdialysis, that Siramesine significantly decreased cocaine-evoked dopamine release in the striatum of freely moving mice. Collectively, these findings demonstrate that sigma-2 receptors regulate neurocircuitry responsible for positive reinforcement and thereby play a role in cocaine-reinforced Pavlovian behaviours.